2017
DOI: 10.21608/resoncol.2017.1333.1033
|View full text |Cite
|
Sign up to set email alerts
|

The Relation between the Severity of Pain and Common Symptoms in Patients with Metastatic Cancer

Abstract: Background: There is a relation between the severity of pain and common symptoms in patients with metastatic cancer. Aim: This study was done to explore this relation among Egyptian patients with advanced cancer. Methods: The study included 120 adult metastatic cancer patients with pain from two cancer centers in Cairo and Sharkia, Egypt. Pain and other common symptoms were assessed using the Arabic version of the Edmonton Symptom Assessment System (ESAS). The Eastern Cooperative Oncology Group (ECOG) performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…Congruent with our results, other researchers found a significant negative relationship between symptom burden and functional status of advanced cancer patients [27][28][29][30][31] . In a recent study from Egypt that included patients with metastatic cancer, the total average ESAS score differed significantly according to the Eastern Cooperative Oncology Group (ECOG) performance scale from 34 in patients with an ECOG score of 1 to 70 in patients with an ECOG score…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Congruent with our results, other researchers found a significant negative relationship between symptom burden and functional status of advanced cancer patients [27][28][29][30][31] . In a recent study from Egypt that included patients with metastatic cancer, the total average ESAS score differed significantly according to the Eastern Cooperative Oncology Group (ECOG) performance scale from 34 in patients with an ECOG score of 1 to 70 in patients with an ECOG score…”
Section: Discussionsupporting
confidence: 58%
“…In this context, little is known about the needs of Egyptian terminal cancer patients 15,26,27 . The current study is one of the few studies that addressed the needs of PC patients in Egypt.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, another study reported that pain was the most common symptom in the diagnosis stage of incurable cancers 22 . Furthermore, most of the patients included in the study were tired (94%), anxious (87.5%), and depressed (83%) 23 . Using the ESAS scale as a guide to identify and understand the main problems can help establish appropriate care for cancer patients 24 .…”
Section: Discussionmentioning
confidence: 99%